DEVELOPMENT OF MODIFIED CUBE BOX FOR LEARNING DESCRIPTIVE TEXT FOR SEVENTH GRADE STUDENTS AT MTS SUBULAS SALAM SELOBEKITI: English - RESA LAILATUL RESA; Tyas Alhim Mubarok; Widiarini (Prodi Tadris Bahasa Inggris, 2023)
The purpose of this research is to develop a modified cube box product with descriptive text chapter material. With this media, the researcher hopes to help English teachers at MTs Subulas Salam in the learning process so that they are more active and easier to achieve learning objectives. Based on observations made by researchers, a problem was found, namely student learning in the dominant class using worksheets so that other media were needed so that learning became more active. The research method used in this article is research and development (R&D), which is a research approach to produce new products or improve existing products. The Rnd method used is the Addie method which consists of 5 steps namely analysis, design, development, implementation, and evaluation. In producing certain products, this research is a needs analysis using survey or qualitative methods. Each product produced also needs to be tested for product feasibility with experimental methods. In accordance with the results that have been carried out, the validation results obtained by the team of experts is 85%. Student response is 89.4%, and teacher response is 90%. With these results it can be concluded that the development of a modified cube box for class VII at MTs Subulus Salam is declared valid and feasible to use.